Pengaruh Edukasi Terhadap Pengetahuan Siswa Tentang Pencegahan Penyebaran Virus Covid-19 - Nurul Aziza Ath Thaariq; Mahdalena Prihatin Ningsih; Lisa Rahmawati; Yuanita Sandra (Poltekkes Kemenkes Padang, 2022)
Coronavirus (CoV) is the cause of respiratory system disease with mild to severe symptoms. The first COVID-19 was reported in Indonesia on March 2, 2020, with as many as two cases. The Indonesian Pediatrician Association West Sumatera recorded that until July 25, 2021, 8,429 children from the age of 0-18 years were attacked by Covid-19. Prevent the transmission by implementing health protocols (wearing masks, washing hands, keeping distance, staying away from crowds, and limiting mobility). Observations show that there are people who do not follow these regulations. The purpose of this study was to determine the effect of education on students' knowledge about preventing the spread of the Covid-19 virus. The type of research used is quantitative research with a quasi-experimental study with a one-group pretest-posttest research design. This study used a group that was given an educational intervention using PowerPoint, video, and demonstrations. Sampling technique with a total population of 36 respondents. Processing data using paired T-test. The average value after being given education (18.17) was higher than before (16.19) with p-value = 0.000. It can be concluded that education affects students' knowledge about preventing the spread of the Covid-19 virus at SDN 17 Gunung Pangilun Padang. The school is advised to implement health protocols in schools to prevent the spread of Covid-19 at SDN 17 Gunung Pangilun Padang.